Menstrual cycle-based undulating periodized program effects on body composition and strength in trained women: a pilot study - Vargas-Molina, S.; Petro, J. L.; Romance, R.; Bonilla, D. A.; Schoenfeld, B. J.; Kreider, R. B.; Benitez-Porres, J. (Science & Sports, 2022)
Objective To evaluate changes in body composition and strength after menstrual cycle-based or traditional undulating resistance training (RT) programs in women. Equipment and methods Ten resistance-trained and eumenorrheic women (26.6 ± 3.0 years; 164.7 ± 6.5 cm; 62.3 ± 6.8 kg) were randomly assigned to a menstrual cycle-based periodized upper/lower training (n = 5, MC) or an undulating training group (n = 5, UT) for 8 weeks. The number of repetitions and load were adjusted to each phase of the menstrual cycle. Fat free mass (FFM) and fat mass (FM) were evaluated by dual x-ray absorptiometry (DXA); maximal strength was assessed by the 1 repetition maximum (1-RM) test in the back squat (SQ) and bench press (BP); and muscle power was assessed by the countermovement jump (CMJ) test using a jump contact mat. Results A significant increase in FFM was observed for UT (1.4 ± 0.9 kg, P = 0.043, ES = 0.58) with no difference in MC (1.7 ± 1.8 kg, P = 0.080, ES = 0.25). No changes in FM were observed for either condition (MC: 0.9 ± 1.2 kg, p = 0.225, ES = 0.21 and UT: 0.5 ± 1.0 kg, P = 0.345, ES = 0.13). Strength increases were observed for both MC an UT in the BP (8.9 ± 3.4 kg, p = 0.042, ES = 0.87 and 5.0 ± 1.8 kg, p = 0.039, ES = 0.67, respectively) and SQ (15.3 ± 9.2 kg, P = 0.043, ES = 0.93 and 16.4 ± 7.6 kg, P = 0.042, ES = 1.38, respectively). CMJ showed differences in MC (4.0 ± 2.5 cm, P = 0.043, ES = 1.12). We observed a between-group difference in BP (P = 0.041) favoring MC; no other interactions were found. Conclusions Eight weeks of a menstrual cycle-based periodized training combined with a hyperenergetic diet versus a non-matched undulating RT program have a differential impact on body composition and muscular adaptations in trained women.